Предмет: Математика,
автор: icommunist1
Помогите решить, знаю, что легко, но что-то я залипла на одном примере... (
Приложения:
Ответы
Автор ответа:
0
1)2a+1a+b - b*(2a+1)b² -a² =2a+1a+b + b*(2a+1)a²-b² =(2a+1)*(1a+b + b(a+b)*(a-b)) =(2a+1)*(a-b+b(a+b)*(a-b))=(2a+1)*(a(a+b)*(a-b)
2)a-b2a+1 *( (2a+1)*a(a-b)*(a+b)) =aa+b
3)aa+b +ba+b =a+ba+b=1
Ответ ------ (Единица)
2)a-b2a+1 *( (2a+1)*a(a-b)*(a+b)) =aa+b
3)aa+b +ba+b =a+ba+b=1
Ответ ------ (Единица)
Автор ответа:
0
)))
Автор ответа:
0
см фото
//////////////////////
//////////////////////
Приложения:
Похожие вопросы
Предмет: Физика,
автор: vikulka30092007
Предмет: Английский язык,
автор: oogaev
Предмет: Математика,
автор: audiovideouser
Предмет: Литература,
автор: Вllадiк